2013
DOI: 10.3762/bjnano.4.90
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis and tunable properties of ultrathin silica nanotubes through spontaneous polycondensation on polyamine fibrils

Abstract: SummaryThis paper describes a facile approach to a biomimetic rapid fabrication of ultrathin silica nanotubes with a highly uniform diameter of 10 nm and inner hollow of around 3 nm. The synthesis is carried out through a spontaneous polycondensation of alkoxysilane on polyamine crystalline fibrils that were conveniently produced from the neutralization of a solution of protonated linear polyethyleneimine (LPEI–H+) by alkali compounds. A simple mixing the fibrils with alkoxysilane in aqueous solution allowed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In comparison, the SiO 2 @LDH showed a centralized distribution, which corresponds to the hollow inner structure of SiO 2 @LDH. The BET results demonstrated that SiO 2 @LDH has an excellent thermal stability compared to the unmodified SiO 2 26, 27. Besides, based on Table 1, the specific surface area of each nanoparticle was 76.82, 122.06, and 25.65 m 2 g −1 , respectively, which suggests the better loading capacity of SiO 2 @LDH.…”
Section: Resultsmentioning
confidence: 94%
“…In comparison, the SiO 2 @LDH showed a centralized distribution, which corresponds to the hollow inner structure of SiO 2 @LDH. The BET results demonstrated that SiO 2 @LDH has an excellent thermal stability compared to the unmodified SiO 2 26, 27. Besides, based on Table 1, the specific surface area of each nanoparticle was 76.82, 122.06, and 25.65 m 2 g −1 , respectively, which suggests the better loading capacity of SiO 2 @LDH.…”
Section: Resultsmentioning
confidence: 94%
“…A considerable number of factors can influence the shape of the primary LPEI aggregates and, consequently, the morphology of the mineralized silica particles. This can be realized by varying the LPEI and/or silica precursor concentration, timespan of silicification [ 19 ], media modulation (i.e., partial replacement of water by methanol or other solvents) [ 20 ], pH value [ 21 ], or by introducing acidic and basic additives that can interact with LPEI [ 22 ] and other proton donors [ 23 ]. Further modification of the silica morphology can be achieved by adding metal ions that form complexes with the secondary amine groups of LPEI [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%